Idiopathic Facial Aseptic Granuloma in a 13-Year-Old Boy Dramatically Improved with Oral Doxycycline and Topical Metronidazole: Evidence for a Link with Childhood Rosacea - Camille Orion; Alicia Sfecci; Laurent Tisseau; Laure Darrieux; Gilles Safa (Karger Publishers, 2016)
Idiopathic facial aseptic granuloma (IFAG) is a rare, benign pediatric dermatological lesion that occurs in children between 8 months and 13 years of age. The pathogenesis of IFAG is still unclear but it is likely to be associated with granulomatous rosacea in childhood. Here we describe a case of IFAG in a 13-year-old boy who showed a dramatic response to oral doxycycline and topical metronidazole, which supports the hypothesis that IFAG may belong to the spectrum of rosacea.